(untitled) (Journal of EAHIL, 2026)
Ever since ChatGPT was launched, we – a writing instructor and a librarian – have been teaching extensively together about generative AI. Our first workshop generated numerous additional workshops for students, teachers, researchers, and administrators – and we were invited to contexts we had formerly not been invited to. We have always focused on AI in relation to searching and writing, but also addressed additional aspects such as AI and learning. Teaching together has added additional value, since our fields of expertise complement each other. In a rapidly changing field, we have focused on collaborative learning, expressed a non-judgemental attitude, and always welcomed discussions. Finally, generative AI has brought our areas of expertise – information literacy and writing – to the top of the agenda.